Innovative research methods in comparative education: emerging trends and applications - Mahendra Prasad ‘Pandey’ (Discover Education)
Abstract Comparative education is advancing with a growing emphasis on innovative research methodologies; however, integrating these approaches to address complex global education challenges remains difficult. While traditional qualitative methods are valuable, they often fail to capture the multifaceted nature of today’s educational landscape. This review examines emerging trends that combine qualitative and quantitative approaches, such as mixed-methods research, big data analytics, longitudinal studies, and meta-analyses, to provide more comprehensive insights. These methodologies play a crucial role in uncovering patterns and supporting evidence-based policymaking by triangulating findings and capturing both the “what” and “why” of educational phenomena. However, their implementation faces significant challenges, including ethical concerns, data privacy issues and contextual disparities across diverse education systems. Resource constraints, particularly in low-income countries, further hinder the widespread adoption of data-intensive methodologies, while ensuring methodological rigor without compromising cultural relevance remains a persistent challenge. Synthesizing studies from 2000 to 2025, this review draws from sources such as Google Scholar, Scopus, Springer, PubMed Central and other journal databases to provide educators, policymakers, and researchers with a critical analysis of advancements in comparative education research, highlighting both their potential and limitations in shaping global educational policies.